Gambaran Kemampuan Refleksi Pembelajaran Mahasiswa Angkatan 2016 Fakultas Kedokteran Universitas Sam Ratulangi - Ruitan, Lidia S.; Manoppo, Firginia M; Wariki, Windy M.V. (Universitas Sam Ratulangi, 2020)
Abstract: Reflection is an integral part of the student-centered approach used in medical education. The learning reflection ability of students needs to be assessed with a valid and reliable instrument. This study aims to determine the reflection ability of batch 2016 students in Faculty of Medicine, Sam Ratulangi University using the Reflection-in-Learning questionnaire. This is a descriptive quantitative study with cross-sectional approach administered to batch 2016 students in Faculty of Medicine, Sam Ratulangi University. Results show that the 95 respondents are in the 18-23 age group, with most respondents being 21 years old (48,8%), followed by 20 years old (34,7%) and 22 years old (8,4%). There are more female respondents (66%) and male respondents (34%). Most respondents fall into the â€œampleâ€ category of learning reflection ability (41,4%), followed by â€œpartialâ€ (24,2%), â€œrestrictedâ€ (17,9%), and â€œminimalâ€ and â€œmaximalâ€ (8,4%). In conclusion, the learning reflection ability of batch 2016 students in Faculty of Medicine, Sam Ratulangi University are mostly in the â€œampleâ€ category, followed by the categories of â€œpartialâ€, â€œrestrictedâ€, and both â€œminimalâ€ and â€œmaximalâ€.Keywords: learning reflection, mahasiswa kedokteranÂ Â Abstrak: Refleksi adalah bagian penting dari pendekatan student-centered yang digunakan dalam pendidikan kedokteran. Kemampuan refleksi pembelajaran mahasiswa dapat diukur dengan instrumen berbentuk kuesioner. Penelitian ini bertujuan untuk mengetahui kemampuan refleksi pembelajaran mahasiswa angkatan 2016 Fakultas Kedokteran Universitas Sam Ratulangi menggunakan Kuesioner Reflection-in-Learning. Penelitian ini bersifat deskriptif kuantitatif dengan pendekatan potong lintang yang dilakukan terhadap mahasiswa angkatan 2016 Fakultas Kedokteran Universitas Sam Ratulangi. Ditemukan bahwa responden yang berjumlah 95 orang berada di rentang umur 18-23 tahun dengan responden terbanyak berumur 21 tahun (48,8%), diikuti dengan 20 tahun (34,7%) dan 22 tahun (8,4%). Responden berjenis kelamin perempuan (66%) lebih banyak daripada laki-laki (34%). Kemampuan refleksi pembelajaran responden terbanyak berada di kategori â€œcukupâ€ (41,4%), diikuti dengan â€œsebagianâ€ (24,2%), â€œterbatasâ€ (17,9%), serta â€œminimalâ€ dan â€œmaksimalâ€ (8,4%). Simpulan penelitian ini ialah kemampuan refleksi pembelajaran mahasiswa angkatan 2016 Fakultas Kedokteran Universitas Sam Ratulangi paling banyak berada di kategori â€œcukupâ€, diikuti dengan kategori â€œsebagianâ€, â€œterbatasâ€, dan â€œminimalâ€ serta â€œmaksimalâ€.Kata kunci: refleksi pembelajaran, mahasiswa kedokteran